Сучасне трактування поняття "проєкт" та його відмінність від бізнес-процесу - Брінь, Павло Володимирович; Абуд, Ахмад Халіль Абуд (Причорноморський науково-дослідний інститут економіки та інновацій, 2019)
Однією з характерних рис сучасного управління є більше використання його проєктно орієнтованої форми. Для більш ефективного застосування проєктно орієнтовного управління необхідними є дослідження поняття "проєкт" як форми організації господарської діяльності та аналіз відмінностей проєкту від бізнес-процесу, що є основними цілями статті. У дослідженні авторами проаналізовано основні сучасні науково-методичні роботи вітчизняних та закордонних вчених у галузі проєктного управління; на базі результатів аналізу визначено основні характеристики проєкту, а саме документарну оформленість, результативність, структурну складність, стратегічність, унікальність, обмеженість у часі, обмеженість ресурсів інноваційність, невизначеність, наявність керівництва та команди проєкту, що дало змогу запропонувати оригінальне визначення поняття "проєкт" та дослідити основні його відмінності від бізнес-процесу.

Today companies’ managers are trying to use all the possible tools to improve the efficiency of business, one of which is project management. The significant benefits of traditional project management, which have been commonly used in industries focused on producing unique results (space, defense, large-scale construction), are becoming popular in areas where this type of management has not been used before. In Ukraine switching to project-oriented management is accelerated by the expansion of American project management theory, the availability of intuitive software, the development of Ukrainian consulting, and the emergence of a large number of enterprises with foreign capital. However, the implementation of project management at domestic enterprises is not as fast as we would like. One of the significant difficulties in using the tools of project management is the misunderstanding by the management of enterprises the essence of “project” and its difference from the business process. Despite the considerable amount of the information in the field of project management, it should be noted that the definition of the term “project” is significantly different in the works of different scientists, and there is a lack of research connected with analyzing on the differences between the project and the business process. The established characteristics allow the authors to propose their own definition of the project. A project is a documented, time-bound set of actions aimed at achieving goals and/or unique results through the use of scarce resources; project implementation is always associated with a high level of uncertainty; project management is carried out by the project manager, who forms a project team that stop existing after the project is completed. The established distinctive characteristics of the project also make it possible to determine its differences from the business process, which is a necessary prerequisite for the use of project management by domestic enterprises. The results of the conducted analysis of the main differences between a project and a business process should simplify the selection of an effective management model.
The modern interpretation of the term “project” and its difference from a business process
Keywords: управління проєктами; характеристики проєктів; бізнес-процеси; стандарт; project management; project characteristics; business process; standard